Redundantly piezo-actuated XYθz compliant mechanism for nano-positioning featuring simple kinematics, bi-directional motion and enlarged workspace. (10th November 2016) - Zhu, Wu-Le; Zhu, Zhiwei; To, Suet; Liu, Qiang; Ju, Bing-Feng; Zhou, Xiaoqin
Abstract: This paper presents a novel redundantly piezo-actuated three-degree-of-freedom XYθ z compliant mechanism for nano-positioning, driven by four mirror-symmetrically configured piezoelectric actuators (PEAs). By means of differential motion principle, linearized kinematics and physically bi-directional motions in all the three directions are achieved. Meanwhile, the decoupled delivering of three-directional independent motions at the output end is accessible, and the essential parallel and mirror symmetric configuration guarantees large output stiffness, high natural frequencies, high accuracy as well as high structural compactness of the mechanism. Accurate kinematics analysis with consideration of input coupling indicates that the proposed redundantly actuated compliant mechanism can generate three-dimensional (3D) symmetric polyhedral workspace envelope with enlarged reachable workspace, as compared with the most common parallel XYθ z mechanism driven by three PEAs. Keeping a high consistence with both analytical and numerical models, the experimental results show the working ranges of ±6.21 μ m and ±12.41 μ m in X - and Y -directions, and that of ±873.2 μ rad in θ z -direction with nano-positioning capability can be realized. The superior performances and easily achievable structure well facilitate practical applications of the proposed XYθ z compliant mechanism in nano-positioning systems.